Nontrivial periodic solutions in the modelling of infectious disease - Wong, Patricia Jia Yiing (2021)
The modelling of the spread of infectious disease is discussed for time t in the real (R), discrete (Z) and time scale (T) domains. We shall offer criteria for the existence of a nontrivial and nonnegative periodic solution for the model in all the three domains. These criteria can be implemented numerically and an algorithm is given.